Microstructural tuning: A route towards realization of enhanced pyroelectric figure of merits of Sr and Zr doped barium titanate ceramics. (June 2022) - Aggarwal, Mehak; Singh, Arun Kumar; Dhiman, Shobhna; Sharma, Gyaneshwar; Thakur, O.P.; Kumar, Sanjeev
Abstract: In this article, we emphasize microstructural tuning approach to realize an enhanced pyroelectric energy conversion associated figure of merits (FOMs) in ferroelectric Ba0.85 Sr0.15 Zr0.1 Ti0.9 O3 (BSZT) ceramics. To develop porous microstructure in the ceramics, we employ BURPS (burning out of polymer sphere) technique using PMMA as a pore-forming agent. In present scenario, the porosity in the ceramics is intentionally being introduced for the noble cause of enhancement in pyroelectric figure of merits ( F e *, Fe, F v ). Here, we investigate the effect of porosity on structural, morphological, dielectric and ferroic characteristics and its correlation with pyroelectric property. We note that, in comparison to dense ceramic, the porous ceramics with 6.9% porosity level shows remarkable enhancement of 29% in F e *, 24% in F e, 53% in F v at 303 K. The microstructural engineering in pyroelectric/ferroelectric ceramics opens the effective route towards the realization of high piezoelectric and pyroelectric figure of merits. Ferroic ceramics with good figure of merit are highly anticipated for their decisive role in the area of green energy harvesting, energy storage and infrared detection. Graphical Abstract: ga1 Highlights: Porous BSZT ceramic with high pyroelectric figure of merits were prepared using PMMA as pore forming agent. Arrott plot technique evidences that interfacial depolarizing factor increases with the rise in porosity. The settlement of normalized entropy curve with two temperature reference insights that porosity modifies the polar dynamics of the ceramics. Porous BSZT with 6.9% porosity level shows remarkable enhancement of 29% in F e *, 24% in F e, 53% in F v at 303 K.